THE EFFECTS OF TOURISM ON VERNACULAR HOUSES IN TRADITIONAL VILLAGE: THE COMPARISON BETWEEN KAMPUNG NAGA IN WEST JAVA AND DESA KANEKES IN BANTEN - Muhammar Khamdevi (Universitas Muhammadiyah Jakarta, 2016)
ABSTRACT. Tourism is one of the significant economic sectors in Indonesia. It has major, economic, social and environmental impacts. However, it may become unsustainable tourism, if its management ignores environmental issues, especially the degradation of the cultural heritage environment. Kampung Naga in West Java and Desa Kanekes in Banten are two cultural heritage villages that became tourist attractions in Indonesia. Their vernacular houses experienced several shifts and changes since then. How are the effects of tourism in Kampung Naga and Desa Kanekes on their vernacular houses? Are there any differences between both of them? A comparative approach is adopted in investigating the cases. This study is expected to find the implementation of current tourism in both villages and its effects on vernacular houses. The study shows that unsustainable tourism is occurred in both locations and result several concerned effects on their vernacular houses.Keywords: sustainable tourism, cultural heritage, vernacular architectureABSTRAK. Pariwisata adalah salah satu sektor ekonomi penting di Indonesia. Ia memiliki dampak ekonomi, sosial dan lingkungan. Meskipun begitu, ia menjadi pariwisata tidak berkelanjutan, jika pengelolaannya mengabaikan isu-isu lingkungan, terutama penurunan kualitas lingkungan warisan budaya. Kampung Naga di Jawa Barat dan Desa Kanekes di Banten adalah dua kampung warisan budaya yang menjadi tujuan wisata di Indonesia. Rumah-rumah vernakularnya mengalami pergeseran dan perubahan sejak saat itu. Bagaimana pengaruh pariwisata di Kampung Naga dan Desa Kanekes pada rumah-rumah vernakularnya? Apakah ada perbedaan di antara keduanya? Pendekatan komparatif dipakai untuk menyelidiki kasus tersebut. Kajian ini diharapkan untuk menemukan pelaksanaan pariwisata saat ini di kedua kampung dan pengaruhnya pada rumah-rumah vernakularnya. Hasil kajian menunjukkan bahwa pariwisata yang tidak berkelanjutan terjadi di kedua lokasi dan menghasilkan beberapa pengaruh-pengaruh yang memprihatinkan pada rumah-rumah vernakularnya.Kata Kunci: pariwisata berkelanjutan, warisan budaya, arsitektur vernakular